The Use of Lasers in Disinfection and Cleaning of Root Canals: a Review - Ivona BAGO JURIČ; Ivica Anić (University of Zagreb. School of Dental Medicine, 2014)
The outcome of root canal treatment is based on efficient disinfection of the root canal system and prevention of reinfection. Current chemomechanical cleaning methods do not always achieve these goals, and insufficient root canal disinfection is the main reason for endodontic failure. Due to high energy content and specific characteristics of laser light, laser treatment has been proposed for cleaning and disinfecting the root canal system. This paper reviews the literature covering the effect of Er:YAG, Er,Cr:YSGG, Nd:YAG and diode laser on the root canal wall in the removal of smear layer and against intracanal bacteria. Recently, the use of laser energy to induce cavitation and acoustic streaming of intracanal irrigants has been investigated. Based on recent literature, it can be concluded that lasers have bactericidal effects. However, they still cannot replace sodium hypochlorite and should be considered as an adjunct to the current chemical root canal disinfection protocols. Certain lasers can help in removing the smear layer and debris and can modify the morphology of the root canal wall. Unfortunately, there have not been enough randomized clinical studies evaluating endodontic treatment outcome following the use of laser.